3p+11/16+2p-3/7=p+3/8+3p-1/14
Answers
Answered by
4
Here we go with the solution
3p +11/16 +2p -3/7 = p +3/8 + 3p -1/14
⇒ p = 3/8 + 3/7 - 11/16 - 1/14
⇒ p = (42 +48 - 77 - 8)/112
⇒p = (90 - 85)/112
⇒p = 5/112
S, the answer to your question will be 5/112.
Hope this answer helps and please mark it for brainliest answer.
3p +11/16 +2p -3/7 = p +3/8 + 3p -1/14
⇒ p = 3/8 + 3/7 - 11/16 - 1/14
⇒ p = (42 +48 - 77 - 8)/112
⇒p = (90 - 85)/112
⇒p = 5/112
S, the answer to your question will be 5/112.
Hope this answer helps and please mark it for brainliest answer.
Similar questions
Science,
8 months ago
Social Sciences,
8 months ago
English,
1 year ago
Math,
1 year ago
Math,
1 year ago